The Role of An Agile Manufacturing Strategy in Managing Environmental Costs According to Sustainability Accounting Standards - Hadi Mohi Hassoun Al-Mansouri, Sadiq; Mahdi Jawad Al-Kawaz, Salah; Aidan Barak Al-Mamouri, Jasim (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the potential role of agile manufacturing strategy in improving environmental cost management in light of sustainability accounting standards. Three techniques—Environmental Life Cycle Costing, Time-Driven Environmental Activity-Based Costing, and Green Target Costing—were applied to actual data from Al-Noura Factory in Karbala for the year 2024. Analytical results indicate the possibility of reducing production costs by 22,687 IQD per ton and decreasing emissions by 37.9% if proposed improvements in fuel mix and raw materials are adopted. The study proposes an integrated model that helps industrial firms balance profitability and sustainability, transforming environmental costs from a financial burden into a strategic investment. The findings confirm that integrating environmental accounting techniques with sustainability standards provides a robust informational foundation to support the transition toward agile manufacturing.